Rasagiline in treatment of Parkinson’s disease - Nayak, Lakshmi (Dove Medical Press, 2008)
Rasagiline (N-propargyl-1 (R)-aminoindan) is a novel propargylamine, irreversible, selective monoamine oxidase inhibitor for treatment of Parkinson’s disease (PD), a progressive condition associated with degeneration of dopaminergic neurons in the substantia nigra. Rasagiline inhibits striatal dopamine metabolism, thereby providing relief from motor symptoms of PD. It may be dosed once daily and, unlike selegiline, it is metabolized to non-amphetamine compounds. In a large clinical trial, rasagiline has proved effective, safe, and well tolerated in early PD as monotherapy. In two phase III clinical trials in advanced PD with motor fluctuations, rasagiline as an adjunct to levodopa significantly decreases “off” time. In animal models of PD, data supports a neuroprotective effect of rasagiline, and its active metabolite aminoindan. Analysis of delayed-start clinical trial suggests the potential for disease modification, and further trials are examining this effect.